Analisis Perlindungan Hukum Terhadap Debitor Dengan Jaminan Fidusia Atas Kendaraan Bermotor Di Indonesia - Abdul Muin; Iwan Hermawan; Tamin Tisna; Firman Nurdiyansyah Sunandar (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Financial institutions, both banks and non-banks, play a strategic role in business transactions in today's modern era. Almost no business activity today requires the services of financial institutions and banks, as the current transaction system is slowly shifting from manual transactions to digital transaction systems using electronic devices and internet connections. This reality is triggered by several reasons, including the fact that digital transaction systems are seen as providing greater convenience, speed, and practicality because they can be done anytime and anywhere without being limited by space and time. In providing credit, there is certainly an agreement and also a guarantee. One well-known guarantee institution is